Analisa Percepatan Dengan Metode Time Cost Trade Off Pada Proyek Pembangunan SPBI 2 × 200 Kl - Sakinah, Sakinah; Mazpar, Ely; Mulyati, Ely (Universitas Sulawesi Tenggara, 2025)
The SPBI 2×200 KL construction project, initially planned to be completed in 360 days, experienced significant delays in the 21st week, with a progress deviation of -16.434%. To address this issue, the Time Cost Trade Off (TCTO) acceleration method was implemented by adding 4 hours of overtime work per day. This strategy successfully shortened the project duration from 336 days to 231 days, reducing the total project time by 37%. The acceleration efforts were focused on critical paths that influenced the project's completion. Although there was a 17.1% increase in direct costs due to overtime wages, additional labor, and extra materials, the application of TCTO effectively reduced indirect costs associated with prolonged project duration, such as administrative and operational expenses. Overall, this method proved to be effective in bringing the project back on schedule and preventing further losses due to delays.